2013
DOI: 10.1152/ajplung.00152.2012
|View full text |Cite
|
Sign up to set email alerts
|

T cell depletion protects against alveolar destruction due to chronic cigarette smoke exposure in mice

Abstract: The role of T cells in chronic obstructive pulmonary disease (COPD) is not well understood. We have previously demonstrated that chronic cigarette smoke exposure can lead to the accumulation of CD4(+) and CD8(+) T cells in the alveolar airspaces in a mouse model of COPD, implicating these cells in disease pathogenesis. However, whether specific inhibition of T cell responses represents a therapeutic strategy has not been fully investigated. In this study inhibition of T cell responses through specific depletin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 126 publications
(128 reference statements)
4
22
0
Order By: Relevance
“…Antiinflammatory drugs salmeterol and fluticasone or increased indoleamine 2,3-dioxigenase activity have been reported to reduce severity of COPD symptoms by enhancing Treg activity (27,28). A recent study in a mouse model of chronic cigarette smoke exposure has shown that therapeutic inhibition of effector T cells protected mice from alveolar destruction and the development of emphysema; a similar approach may be efficacious for COPD (29). Our studies suggest the dual nature of Tregs in COPD.…”
Section: Garpsupporting
confidence: 53%
“…Antiinflammatory drugs salmeterol and fluticasone or increased indoleamine 2,3-dioxigenase activity have been reported to reduce severity of COPD symptoms by enhancing Treg activity (27,28). A recent study in a mouse model of chronic cigarette smoke exposure has shown that therapeutic inhibition of effector T cells protected mice from alveolar destruction and the development of emphysema; a similar approach may be efficacious for COPD (29). Our studies suggest the dual nature of Tregs in COPD.…”
Section: Garpsupporting
confidence: 53%
“…Our data suggest that animals with chronic airflow limitation had significantly raised levels of various systemic inflammatory markers like circulating leukocytes (specifically T-cells and neutrophils) and serum TNF-␣ level, indicating that persistent systemic inflammation is present in AKR/J. LGF treatment decreases T-lymphocyte population in peripheral blood, what seems to be in agreement with a recently published article that shows that T-cell depletion protects against alveolar destruction attributable to chronic CSE in mice (37). It is possible in some cases that the inflammatory process may "spill" over into the systemic circulation, promoting a generalized inflammatory reaction.…”
Section: Discussionsupporting
confidence: 91%
“…It is possible in some cases that the inflammatory process may "spill" over into the systemic circulation, promoting a generalized inflammatory reaction. Our findings are consistent with systemic inflammation present in some patients with COPD (1) associated with an increased influx of T-cells into the airway (6,28,31,37). This finding may explain, at least in part, the high prevalence of systemic complications, such as cachexia, osteoporosis, and cardiovascular diseases among patients with COPD.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, T cell responses have been shown to be important in COPD. Podolin et al (113) found that T cell depletion in a mouse model of COPD inhibited alveolar destruction caused by chronic cigarette smoke exposure. Cigarette smoke has been shown to induce reversible changes in energy metabolism and the cellular redox status that are not related to the inflammatory responses in mouse lung (6).…”
Section: Inflammatory Responses In Cf and Copdmentioning
confidence: 99%